Предмет: Математика, автор: Аноним

20 балов решениепошагово

Приложения:

Ответы

Автор ответа: nanoonan16th
1

Ответ:

\frac{9}{4}

Пошаговое объяснение:

(9\frac{1}{4}-8\frac{2}{3})*1\frac{5}{7}+(4\frac{2}{9}-2\frac{5}{6}):1\frac{1}{9}=\\\\(\frac{37}{4}-\frac{26}{3})*\frac{12}{7}+(\frac{38}{9}-\frac{17}{6}):\frac{10}{9}=\\\\(\frac{37*3-26*4}{12})*\frac{12}{7}+(\frac{38*2-17*3}{18}):\frac{10}{9}=\\\frac{7}{12}*\frac{12}{7}+\frac{25}{18}*\frac{9}{10}=\\1+\frac{5}{2}*\frac{1}{2}=1+\frac{5}{4} =\frac{9}{4}

Автор ответа: grinvalya2001
0

Відповідь:

Покрокове пояснення:

Приложения:
Похожие вопросы